FAKTOR YANG MEMPENGARUHI KESEDIAAN PELAJAR MENGGUNAKAN ANGKUTAN SEKOLAH DI KOTA TEGAL - Sugiyarto, Tino (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2023)
The large number of students using motorbikes as a mode of going to school is concerning because this condition will endanger the students' safety. To reduce the level of motorcycle use among students, providing school transportation facilities is necessary so that they can reduce traffic accidents among adolescents. This study aimed to determine the existing conditions of student travel behavior and determine what factors influence students' readiness to use school transportation services. The analytical method used is descriptive statistical analysis. The study results show that many students in Tegal City, especially junior and senior high schools, use motorbikes to go to school. In addition, factors such as age, pocket money, parents' income, distance, and travel time affect students' approval to use school transportation services